Validitas Pop-up Book sebagai Media Pembelajaran Biologi Sekolah Menengah Atas - Sari, Linda Purnama (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Learning media is an intermediary or messenger between a teacher and students. This learning media is very necessary in stimulating thoughts, feelings and attention, as well as interest, so that it can facilitate the delivery of educational material. The aim of this research is to determine the validity of Pop-up Books as a biology learning medium in high schools. This type of research is development research using the 4-D model (Define, Design, Develop, Disseminate). However, in this research, the author only used it up to the development stage. The author focuses on the development stage to produce products that are effective and relevant to user needs. The instrument used in this research was a validation sheet. The data collection technique is validation, the media that has been prepared is validated by three validators, namely material expert validator, media expert validator, and language expert validator. The data analysis technique used is the percentage technique. Based on the validation results from three validators, namely media experts obtained a percentage of 72%, material experts 83%, and 80% from language experts, with an average percentage of 78.3%. Thus, the Pop-up Book media is declared valid and suitable for use as a biology learning media in high schools.